Language anxiety in learning english among undergraduates in UNIMAS - Lee, Yung Fook (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study aimed at finding out the language anxiety level and major factor causing language anxiety in UNIMAS. This study aimed to find out the language anxiety level, whether there are differences in anxiety level among undergraduates in UNIMAS in terms of gender, proficiency level and stream. This study also was set out to investigate the major factor that caused anxiety among sample. Self-rating questionnaire was used to probe levels of language anxiety and major language anxiety factor of 226 respondents, who were undergraduates from seven faculties in UNIMAS. The results showed that majority of the students encountered average level of language anxiety. 73.7% of the students experienced moderate level of language anxiety. The result revealed that variable gender did not influence the anxiety levels of 88 males and 138 females. Variable stream also did not influence the anxiety levels of 129 art students and 97 sciences students. However, the result showed that variable of proficiency levels influenced the anxiety levels of 113 high proficiency students and 113 low proficiency students. Low proficiency students have higher anxiety level from those high English proficiency students. The result revealed that three factors have contributed to their anxiety, namely fear of failing, lack of preparation, and lack of confidence. Fear of failing the class is the major factor of language anxiety.